2022
DOI: 10.3389/fevo.2022.841744
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Arrival Time of White Storks (Ciconia ciconia L.): Impact of Age, Interindividual Variation, and Global Change

Abstract: Global changes are inducing migratory birds to advance their annual cycle. However, changes in the time of arrival at their breeding grounds have significant fitness implications. This study aims to identify factors affecting the variability in arrival time of migratory white storks (Ciconia ciconia L.) and to determine if their arrival at North African breeding grounds is occurring earlier. We monitored the arrival of ringed white storks at a breeding colony in Algeria between 2017 and 2021. The birds arrived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Our estimate of conspecific density is biased towards younger individuals. However, we are also confident that this is a realistic representation of the white stork’s proportions during migration 69,7678 . As detailed above (see Subject Details), there are large numbers of juveniles and high mortality rates.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Our estimate of conspecific density is biased towards younger individuals. However, we are also confident that this is a realistic representation of the white stork’s proportions during migration 69,7678 . As detailed above (see Subject Details), there are large numbers of juveniles and high mortality rates.…”
Section: Methodsmentioning
confidence: 69%
“…69,[76][77][78] .As detailed above (see Subject Details), there are large numbers of juveniles and high mortality rates. Thus, our estimated density is just a sample of the entire population but its temporal development (i.e.…”
mentioning
confidence: 99%
“…The authors suggested that the signi cant interaction could indicate that the sexes enter the reproductive population at different ages. Younger individuals were shown to arrive later at the breeding grounds [48,80,95], and therefore they have to choose among the available nests potentially in suboptimal territories or even establish new nests that are less frequently reoccupied [96]. Moreover, males tend to arrive before females on the breeding grounds [48], and according to Vergara et al [29], it could explain the weak sex differences in nest-site delity.…”
Section: Discussionmentioning
confidence: 99%
“…The results also show a significant correlation between FIDs of breeding white storks and the date (1 = 1 January) of the year, age, and presence or absence of a breeding partner. Egg-laying occurs between the second half of February and early May, and breeding date is strongly associated with arrival date and age [ 41 , 42 , 45 ]. The significant relationship between FID and reproductive stage found in white storks ([ 40 ], this study) and great egrets ( Ardea alba ) [ 46 ] is partially consistent with the offspring value hypothesis [ 10 , 47 ], which states that parents make decisions that maximize their overall reproductive fitness, including both current and future reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, chicks are fitted with uniquely coded Darvic PVC rings prior to fledging as part of a chick ringing program. Our experiment was conducted at this colony ( Figure 1 a), which hosts approximately two hundred breeding pairs annually and has served as a study site for ecological studies since 2011 [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%